Maturation of bovine cumulus oocyte complexes in follicular fluid with or without estradiol, progesterone or the combination affects cumulus cell expansion and blastocyst development - Audra W. Harl; Verónica M. Negrón-Pérez; Jacob W. Stewart; George A. Perry; Alan D. Ealy; Michelle L. Rhoads (PLoS ONE, 2025)
Although laboratory procedures for in vitro bovine embryo production have improved immensely, developmental capacity following fertilization is still limited, especially in comparison to in vivo-produced embryos. In vivo, the maturing oocyte is enclosed in the ovarian follicle and surrounded by its cumulus cells and follicular fluid. Hormones and other components of the follicular fluid change dynamically as the follicle develops and approaches ovulation. The importance of the in vivo follicular microenvironment for oocyte developmental competence has not been well defined, however. Therefore, the objective of this study was to investigate the impact of follicle size and relative estradiol and progesterone concentrations on cumulus cell expansion and early embryo development following follicular fluid exposure during maturation in vitro. All experiments and replicates contained a standard formulation control maturation medium (cOMM). Follicular fluid was collected via needle aspiration from small (2–5 mm diameter) and large (10–20 mm diameter) follicles and pooled according to size. The follicular fluid was added to a hormone-free base medium (eOMM) as follows: supplemented with 75% untreated large follicular fluid (LFF75), 75% untreated small follicular fluid (SFF75), 75% charcoal-stripped large follicular fluid (csLFF75), 75% charcoal-stripped small follicular fluid (csSFF75). Progesterone and/or estradiol were added to the charcoal-stripped follicular fluid treatments based on average concentrations found in fluid from pooled large or pooled small follicles. These six treatment media were formulated using eOMM as a base with the following designations and additions: 75% charcoal-stripped large follicular fluid + 37 ng/ml estradiol (csLFF+E2), 75% charcoal-stripped small follicular fluid + 23 ng/ml estradiol (csSFF+E2), 75% charcoal-stripped large follicular fluid + 160 ng/ml progesterone (csLFF+P4), 75% charcoal-stripped small follicular fluid + 140 ng/ml progesterone (csSFF+P4), 75% charcoal-stripped large follicular fluid + 37 ng/ml estradiol + 160 ng/ml progesterone (csLFF+E2+P4), or 75% charcoal-stripped small follicular fluid + 23 ng/ml estradiol + 140 ng/ml progesterone (csSFF+E2+P4). Cumulus expansion in the csSFF75 maturation medium was less than that of its untreated counterpart (SFF75), while cumulus cell expansion was similar for LFF75 and csLFF75. The addition of estradiol to the follicular fluid treatments was beneficial and improved cumulus cell expansion to values similar to cOMM, while progesterone alone had no effect. The greatest cumulus cell expansion was observed when both estradiol and progesterone were added to the follicular fluid treatments. Cleavage rates were generally reduced by follicular fluid treatments, with the exception being csSFF+P4 which had a cleavage rate similar to oocytes matured in cOMM. Blastocyst rates for LFF75 and csLFF75 were similar to cOMM, while SFF75 and csSFF75 reduced blastocyst rates. Interestingly, the follicular fluid treatments with added progesterone either maintained or improved blastocyst rates such that csLFF+P4 and csSFF+P4 were similar to cOMM. The same could not be said for any of the treatments containing estradiol, whether alone or in combination with progesterone. Taken together, these results suggest a dichotomous relationship between estradiol and progesterone during maturation. Estradiol supports cumulus cell expansion while progesterone concentrations during oocyte maturation are more important for subsequent embryo development.